2009
DOI: 10.1080/10408440902969430
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tunica vaginalis mesotheliomas in rats by xenobiotics

Abstract: To better understand the relevance of tunica vaginalis mesotheliomas (TVM) to human cancer risk, we examined the nature of TVM responses in 21 published rat cancer bioassays against the backdrop of the biology and molecular biology of mesothelium, and of spontaneous and treatment-induced TVM. Although relatively rare in all species including humans, TVM are seen most frequently in F344 male rats, as opposed to other rat strains, and are causally associated with the high background incidence of Leydig-cell tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 118 publications
0
38
0
Order By: Relevance
“…In this study, we followed the established protocol to generate iron-induced peritoneal mesothelioma, 8,22 and analyzed the generated tumors using two different microarray techniques. An iron chelator, nitrilotriacetate, has been used in this fiberunassociated mesothelioma model to mobilize the catalytic form of iron from deposits.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we followed the established protocol to generate iron-induced peritoneal mesothelioma, 8,22 and analyzed the generated tumors using two different microarray techniques. An iron chelator, nitrilotriacetate, has been used in this fiberunassociated mesothelioma model to mobilize the catalytic form of iron from deposits.…”
Section: Discussionmentioning
confidence: 99%
“…In a review by Maronpot et al (2009) on TVM, it was stated that both TVM and Leydig cell tumours are seen most frequently in F344 rats as opposed to other rat strains used in carcinogenicity bioassays.…”
Section: Modes Of Action Of Carcinogenicitymentioning
confidence: 99%
“…In addition, there is an apparent association with the high background incidence of testicular Leydig-cell tumors of these rats. It has been suggested that hormone imbalance brought about by perturbations of the endocrine system is a key factor leading to both spontaneous and exposure-associated mesotheliomas in the tunica vaginalis (Maronpot et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence in the 500-ppm dose group was significantly increased relative to controls, but the incidence in this group exceeded the historical control range by only a single neoplasm. Mesothelioma is a relatively common neoplasm of F344/N male rats, and the tunica vaginalis is the most common site of origin, whether occurring spontaneously or as an exposure-related lesion (Maronpot et al 2009). In addition, there is an apparent association with the high background incidence of testicular Leydig-cell tumors of these rats.…”
Section: Discussionmentioning
confidence: 99%